STATE SUPPORT MEASURES OF JOB CREATION IN THE AGROINDUSTRIAL COMPLEX OF UZBEKISTAN (World Bulletin of Social Sciences, 2024)
The article examines the creation of jobs in the agriculture of Uzbekistan, employment in agriculture, and the impact on poverty reduction, since 80% of the low-income population of Uzbekistan live in rural areas. Measures of state support for creating jobs in the agro-industrial complex of Uzbekistan are being considered
Keywords: agricultural sector; employment; state policy; government spending